Digital Assessment Tools for Special Education Teachers: Challenges and Opportunities - Sanal, Seda Ozer (My University, 2023)
This study was conducted to reveal the views of special education teachers on digital assessment tools. The researcher collected data from 38 special education teachers through focus group interviews. The opinions were coded under two main themes: challenges and opportunities. Under the main theme of challenges, there are sub-themes of knowledge and skills, curriculum, time, integration, collaboration, management and cost. Under the main theme of opportunities, there are sub-themes of virtual classroom, digital bag, new collaborations, paperless classroom, diversity of approaches, individualized exams, active learning and feedback. The themes are discussed within the scope of instructional technologies, current literature on special education and recommendations are included.
Keywords: Eğitim; Özel